Selecting Pigs for Youth Swine Shows - Timothy T. Marshall; William R. Walker; David L. Prichard; Saundra H. TenBroeck (EDIS)
This publication will help youth exhibitors determine how and where to purchase a project pig and provide information on what the student should look for when purchasing the pig in order to do well in a swine show. This document is 4HSWG04 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Reviewed June 2002.